Ureter tissue engineering with vessel extracellular matrix and differentiated urine-derived stem cells. (1st April 2019) - Zhao, Zhankui; Liu, Deqian; Chen, Ye; Kong, Qingsheng; Li, Dandan; Zhang, Qingxin; Liu, Chuanxin; Tian, Yanjun; Fan, Chengjuan; Meng, Lin; Zhu, Haizhou; Yu, Honglian
Graphical abstract: Abstract: Objective: To assess the possibility of ureter tissue engineering using vessel extracellular matrix (VECM) and differentiated urine-derived stem cells (USCs) in a rabbit model. Methods: VECM was prepared by a modified technique. USCs were isolated from human urine samples and cultured with an induction medium for the differentiation of the cells into urothelium and smooth muscle phenotypes. For contractile phenotype conversion, the induced smooth muscle cells were transfected with the miR-199a-5p plasmid. The differentiated cells were seeded onto VECM and cultured under dynamic conditions in vitro for 2 weeks. The graft was tubularized and wrapped by two layers of the omentum of a rabbit for vascularization. Then, the maturated graft was used for ureter reconstruction in vivo . Results: VECM has microporous structures that allow cell infiltration and exhibit adequate biocompatibility with seeding cells. USCs were isolated and identified by flow cytometry. After induction, the urothelium phenotype gene was confirmed at mRNA and protein levels. With the combined induction by TGF-β1 and miR-199a-5p, the differentiated cells can express the smooth muscle phenotype gene and convert to the contractile phenotype. After seeding cells onto VECM, the induced urothelium cells formed a single epithelial layer, and the induced smooth muscle cells formed a few cell layers during dynamic culture. After 3 weeks of omental maturation, tubular graft was vascularized. At 2 months post ureter reconstruction, histological evaluation showed a clearly layered structure of ureter with multilayered urothelium over the organized smooth muscle tissue. Conclusion: By seeding differentiated USCs onto VECM, a tissue-engineered graft could form multilayered urothelium and organized smooth muscle tissue after ureteral reconstruction in vivo . Statement of significance: Cell-based tissue engineering offers an alternative technique for urinary tract reconstruction. In this work, we describe a novel strategy for ureter tissue engineering. We modified the techniques of vessel extracellular matrix (VECM) preparation and used a dynamic culture system for seeding cells onto VECM. We found that VECM had the trait of containing VEGF and exhibited blood vessel formation potential. Urine-derived stem cells (USCs) could be differentiated into urothelial cells and functional contractile phenotype smooth muscle cells in vitro . By seeding differentiated USCs onto VECM, a tissue-engineered graft could form multilayered urothelium and organized smooth muscle tissue after ureteral reconstruction in vivo . This strategy might be applied in clinical research for the treatment of long-segment ureteral defect.